Isolation, identification and characterisation of sulphur-oxidising bacteria isolated from hot spring for reduction of hydrogen sulphide in chicken manure - Mohd. Yusof, Hidayat (2017)
The rapid development of poultry industry has led to the production of large amounts of manure which contributed to odour pollution such as hydrogen sulphide (H2S). Hydrogen sulphide is widely known as the most undesirable gas component and therefore, H2S removal from the environment is necessary. Generally, chemical and physical methods have been used for the removal of H2S, however, this method is costly and often results in secondary pollution. Recently, the biological method has drawn so much attention due to its efficiency, low-cost method, and environmentally friendly. It has been widely known that sulphur oxidising bacteria (SOB) can be used to remove contaminating H2S due to its ability to oxidise the reduced sulphur compounds. Thus, this study was conducted to isolate, characterise and identify a potential SOB from hot spring in Malaysia in reducing the H2S from chicken manure. Three potential SOB has been isolated in this work which namely as isolate AH18, AH25, and AH28. Isolate AH18 was identified as Pseudomonas sp. meanwhile isolate AH25 and AH28 was identified as Achromobacter sp. based on 16S rRNA phylogenetic analysis. The optimum pH for growth of all the isolates occurred at pH 8.0. Moreover, the optimum temperature for isolate AH18, AH25 and AH28 occurred at 45 °C, 30 °C and 30-45 °C respectively. The three isolates were classified as facultative chemolithotroph with the capability of growth at thiosulphate concentration as high as 100 mM. The pure culture and the mixed culture of the isolates were immobilised on perlite and alginate for cell immobilisation to test their H2S removal performance in chicken manure. The laboratory-scale experiments revealed that the most active isolate was AH18 with a reduction rate of 67.3% and 74.7% when carried on perlite and alginate respectively. Meanwhile, the reduction rate for isolate AH25 was 59% and 54.2% when carried on perlite and alginate respectively, and for isolate AH28 was 63.2% and 60.8% when carried on perlite and alginate respectively. However, the removal performance of H2S was enhanced in mixed culture with 69.6% and 81.9% of reduction rate carried on perlite and alginate respectively. Additionally, based on the results obtained, the reduction rate of H2S in chicken manure was observed higher when the potential SOB and the mixed culture were carried on alginate than on perlite. In conclusion, three potential SOB isolates were successfully isolated from hot spring in Malaysia with their ability in reducing the H2S from chicken manure in the form of pure culture and mixed culture. Moreover, based on the results obtained, these potential SOB isolates could be a potent candidate for biological deodorisation due to their pH, temperature adaptability, metabolic flexibility and H2S removal efficiency in chicken manure. In addition, to achieve the higher H2S removal ability, the mixed culture carried on alginate could be the best alternative for H2S deodorisation application.